2021
DOI: 10.3928/01477447-20201012-04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Readability of Online Patient Education Materials Related to Orthopedic Oncology

Abstract: The internet is increasingly used to access patient education materials. The average American reading level has been found to be that of a 7th- to 8th-grade student, prompting the National Institutes of Health (NIH) and the American Medical Association (AMA) to advise that patient education materials be written between the 4th- to 6th-grade reading level. The purpose of this study was to evaluate the reading level of current patient education materials for the most common musculoskeletal oncological tumors. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Despite these recommendations, prior studies have elucidated the readability of patient education materials, with many studies describing that the average reading levels of education materials do not meet the national recommended average by several grade levels. 6,7,[9][10][11][12][13][14][15][16][17][18][19][20] In prior studies, it is clear that many patient education materials are written above the recommended levels; however, to our knowledge, this is the first study to offer a simplified solution using AI to manage and improve patient health education materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these recommendations, prior studies have elucidated the readability of patient education materials, with many studies describing that the average reading levels of education materials do not meet the national recommended average by several grade levels. 6,7,[9][10][11][12][13][14][15][16][17][18][19][20] In prior studies, it is clear that many patient education materials are written above the recommended levels; however, to our knowledge, this is the first study to offer a simplified solution using AI to manage and improve patient health education materials.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Although patient education materials, such as brochures and web pages, aim to provide patients with relevant information, they often require an above-average reading level to understand. 6,7 A 2020 Gallup analysis found that about 54% of Americans between the ages of 16 and 74 read below a sixth grade level. To address this, the American Medical Association recommends that readability of patient education materials should not exceed a sixth grade reading level.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, multiple studies have shown that both printed and online material aimed at educating patients about medical diagnoses and treatment options far exceeds this level, and therefore are not comprehensible by most patients. [16][17][18][29][30][31] Furthermore, both providers and patients overestimate patients' abilities to comprehend written information presented to them, and therefore many patients are left without adequate understanding of their medical management and inadequately equipped to make medical decisions. 32 Health literacy has been shown to be an important predictor of health outcomes, including higher mortality, worse health-related quality of life, and increased medical costs for the system.…”
Section: Discussionmentioning
confidence: 99%
“…They add to an existing body of literature that suggests that online and written patient educational materials are written at a reading level that is too high for many patients to comprehend. 15,18,30,39,41 Further, they show that social media, which many presume to be easily understandable and accessible to all patients, is still incomprehensible for many. The medical community must continue efforts at ensuring that patient educational materials are comprehensible by patients and assist patients in playing an active role in their healthcare decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation